2019
DOI: 10.1055/s-0039-1683879
|View full text |Cite
|
Sign up to set email alerts
|

Is a Chest Tube Necessary after Video-Assisted Thoracoscopic Mediastinal Tumor Resection?

Abstract: Background The omission of chest tubes after thoracoscopic procedures such as sympathectomy, lung biopsy, and lung resection has proven efficacious in decreasing pain and length of hospital stay in some cases. However, its safety for mediastinal diseases remains unclear. This study evaluated the feasibility and outcome of eliminating chest drains after video-assisted thoracoscopic surgery (VATS) for mediastinal tumor resection. Methods We retrospectively investigated 70 patients receiving VATS medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…Eight studies reported postoperative pleural effusion without the need for drainage or thoracocentesis (27)(28)(29)(32)(33)(34)38,39). From four studies (one was RCT and two were non-RCTs) comprising each 110 patients in both the NCD group and the CD group (29,34,38), with no significant difference between the two groups and not difference on subgroup analysis. There was no heterogeneity among analyses (Table 3, Figure 5).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Eight studies reported postoperative pleural effusion without the need for drainage or thoracocentesis (27)(28)(29)(32)(33)(34)38,39). From four studies (one was RCT and two were non-RCTs) comprising each 110 patients in both the NCD group and the CD group (29,34,38), with no significant difference between the two groups and not difference on subgroup analysis. There was no heterogeneity among analyses (Table 3, Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…Ten studies with 1,079 patients were included, comprising 561 (52.0%) classified as NCD and 518 (48%) as CD. Among these, four (19,(32)(33)(34) were RCTs including 353 patients (33%) and six (27)(28)(29)(30)38,39) were non-RCTs including 726 patients (all retrospective but one). The number of patients for each individual study ranged from 49 to 333.…”
Section: Characteristics Of Studies and Casesmentioning
confidence: 99%
See 2 more Smart Citations
“…We also compared the chest tube stay and the postoperative hospital stay between the two grops and saw a statistically significant difference (p < 0.05). Removing chest drain after VATS may benefit some patients by decreasing postoperative pain and shortening hospital stays, without increasing complications or compromising patient safety [20].…”
Section: Perioperative Difficulties Of This Proceduresmentioning
confidence: 99%